A multicenter study assessing the prevalence of germline genetic alterations in Chinese gastric-cancer patients. (29th May 2021) - Zhang, Yin-Jie; Yang, Yang; Wei, Qing; Xu, Ting; Zhang, Xiao-Tian; Gao, Jing; Tan, Si-Yi; Liu, Bao-Rui; Zhang, Jing-Dong; Chen, Xiao-Bing; Wang, Zhao-Jie; Qiu, Meng; et al.
Abstract: Background: Approximately 10% of patients with gastric cancer (GC) have a genetic predisposition toward the disease. However, there is scant knowledge regarding germline mutations in predisposing genes in the Chinese GC population. This study aimed to determine the spectrum and distribution of predisposing gene mutations among Chinese GC patients known to have hereditary high-risk factors for cancer. Methods: A total of 40 GC patients from 40 families were recruited from seven medical institutions in China. Next-generation sequencing was performed on 171 genes associated with cancer predisposition. For probands carrying pathogenic/likely pathogenic germline variants, Sanger sequencing was applied to validate the variants in the probands as well as their relatives. Results: According to sequencing results, 25.0% (10/40) of the patients carried a combined total of 10 pathogenic or likely pathogenic germline variants involving nine different genes: CDH1 ( n = 1), MLH1 ( n = 1), MSH2 ( n = 1), CHEK2 ( n = 1), BLM ( n = 1), EXT2 ( n = 1), PALB2 ( n = 1), ERCC2 ( n = 1), and SPINK1 ( n = 2). In addition, 129 variants of uncertain significance were identified in 27 patients. Conclusions: This study indicates that approximately one in every four Chinese GC patients with hereditary high risk factors may harbor pathogenic/likely pathogenic germline alterations in cancer-susceptibility genes. The results further indicate a unique genetic background for GC among Chinese patients.